1999
DOI: 10.1149/1.1390631
|View full text |Cite
|
Sign up to set email alerts
|

Air-Gaps for Electrical Interconnections

Abstract: The fabrication of air-gap structures for electrical interconnections has been demonstrated using a sacrificial polymer encapsulated in conventional dielectric materials. The air-gap is formed by thermally decomposing the sacrificial polymer and allowing the byproducts to diffuse through the encapsulating dielectric. The diffusivity of the polymer decomposition products is adequate at elevated temperatures to allow the formation of an air-gap. The decomposition of a 5 µm thick polymer film results in less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…This includes fabrication of air-gaps in electrical interconnects, MEMS, microfluidic devices, and micro-reactors. The formation of air-gaps is important in electrical interconnects because it lowers the effective dielectric constant of the matrix [1]- [5]. The fabrication of buried air-channels is useful for the creation of vias in multi-level wiring boards, micro-display boards with high resolution, and ink-jet printer heads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes fabrication of air-gaps in electrical interconnects, MEMS, microfluidic devices, and micro-reactors. The formation of air-gaps is important in electrical interconnects because it lowers the effective dielectric constant of the matrix [1]- [5]. The fabrication of buried air-channels is useful for the creation of vias in multi-level wiring boards, micro-display boards with high resolution, and ink-jet printer heads.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Moore et al used highly structured dendritic material, specifically, hyperbranched polymers as a dry-release sacrificial material in the fabrication of cantilever beam [8]. Previous work by Kohl et al has demonstrated the fabrication of air-gaps using nonphotosensitive sacrificial polymers that decompose in the range 250-425 C [1], [4]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several processing techniques have been disclosed for forming air-isolation in electronic devices including the use of CMP and via etch [4], etch back technique [7][8], sacrificial polymers [5,6,[10][11][12][13], and wet etching [9]. Among these techniques, the use of a sacrificial polymer for creation of air-gaps is a promising method which can be applied to a variety of applications.…”
Section: Fabrication Of Air-gap Structuresmentioning
confidence: 99%
“…Among these techniques, the use of a sacrificial polymer for creation of air-gaps is a promising method which can be applied to a variety of applications. The fabrication of air-gaps in electrical interconnects based on a sacrificial polymer and plasma-enhanced chemical vapor deposited (PECVD) SiO 2 has been presented by Kohl et al [10][11]. A sacrificial polymer embedded between metal interconnect structures was used.…”
Section: Fabrication Of Air-gap Structuresmentioning
confidence: 99%
“…This type of structure could be used in applications that require hollow channels for fluid or gas plumbing ͑i.e., microfluidics 5 or gas chromatography 6,7 ͒. Air-bridge structures 8 used in microelectronics to create low-dielectric constant regions could also be created using this new fabrication method. Pressure sensing devices that require a movable membrane 9,10 could also be impacted.…”
Section: Introductionmentioning
confidence: 99%